Indigenous and faith healing for mental health in Ghana: An examination of the literature on reported beliefs, practices and use of alternative mental health care in Ghana - Lily Kpobi; Leslie Swartz (AOSIS, 2019)
Background: For many people in African countries, various forms of health care are utilised for the treatment of illness. This pluralistic nature of health seeking includes the use of indigenous, faith and allopathic medicines for care. Aim: In this article, our aim was to gain insight into the existing knowledge on indigenous and faith healing in Ghana, with a particular focus on mental health care. We first examine the reported mental health beliefs and practices of Ghanaian alternative healers. Following this, we look at the use and purported preference for non-biomedical mental health care by patients. Methods: Relevant literature was examined to explore the beliefs, practices and use of non-biomedical mental health care systems in Ghana Results: Evidence for the use and preference for non-biomedical mental health care is largely anecdotal. Similarly, the mental health beliefs of alternative healers have been documented in various small-scale studies. However, such information is important if mental health services in Ghana are to be improved. Conclusion: Integration of the different healthcare systems must be built on knowledge of beliefs and methods. A clearer understanding of the work of non-biomedical healers is important if appropriate recommendations are to be made for collaboration between biomedical and non-biomedical systems in Ghana.